Secure and effective random paths selection (SERPS) algorithm for security in MANETs - Suma, P; Ali Hussain, Mohammed (International Journal of Engineering and Technology, 2018)
Mobile Ad-hoc Networks (MANETs) are wireless and nodes of it are mobile in nature. These networks can be adopted where equipment like wires cannot be established and the nodes are moving. Due to the mobile nature of nodes, a fixed topology cannot be achieved. This leads to a dynamic or ever changing network structure. The paths between the communicating nodes also change frequently. Overall monitoring system is absent in it i.e. supervising node is not present for establishing routes in the network. Each node itself acts as a router. Due to the lack of fundamental management system and ever moving nodes, security becomes a challenge and detection of attackers also becomes tough. Dynamic source Routing (DSR) is used in route discovery. In this routing strategy, paths are established only on demand of sender and receiver nodes. And to reduce the cost many algorithms were proposed, but the concept of security is deficit in them. In this paper, Secure and Effective Random Paths Selection (SERPS) algorithm is proposed with the concepts of minimum cost and node disjointness to achieve security. All the node disjoint paths between sender and receiver are found. Among them a minimum of 4 minimum cost paths are selected. Then data packets are sent through them by randomly selecting the paths. Care is to be taken such that no consecutive packets go through the same path. By this, attacker at any node gets only the random packets but not the complete data. In this way security can be achieved. The simulation for the proposed SERPS algorithm is done to show the routing process.